Student-Centred Teaching Strategies by Gender, Grade Level, and Teacher’s Self-Concept in Mexico - PEDRO SÁNCHEZ-ESCOBEDO; ANA KAREN CAMELO LAVADORES (Indonesian Research Journal in Education |IRJE|, 2018)
This study examined the student-centred teaching strategies of Mexican teachers by gender, grade level, and self-concept as an instructor. A conventional sample of 573 teachers from diverse school settings in the state of Yucatan in Mexico responded to a paper and pencil questionnaire. Results indicated, in general, that teachers prioritized classroom management and independent learning activities, in contrast with teaching strategies emphasized by policies and teacher´s training programs in the country, such as cooperative learning, differentiation, or promoting critical thinking. There were some gender and grade level differences. In general, female teachers promoted more independent activities than males. As expected, primary school teachers were more concerned with using differentiation teaching strategies than secondary education teachers, considering the greatest variance in younger students. Teachers self-concept had differential effects. Whilst self-efficacy feelings had no influence in the use of specific student-centred teaching strategies, high self-esteem teachers used more student-centred teaching strategies. The importance of asking teachers what they did, and how they felt as teachers was argued in light of results. Future research avenues regarding self-concept and teaching strategies are posited.